The Role of Nature Reserves in Ecosystem Services and Urban Ecological Sustainable Development - Haoyu Wu; Fei Song; Haifu Li; Junbo Bai; Lijuan Cui; Fangli Su; Zahra Kalantari; Carla Sofia Ferreira (Land)
With the acceleration of global urbanization, the ecosystem services (ES) and ecological balance of nature reserves have been significantly impacted. However, quantitative assessments of the multiple contributions of nature reserves to urban ecological sustainability are still lacking. This study selects Panjin, a wetland city in China (3788 km2), as the study area, utilizing the InVEST model to quantify ES (water yield, carbon storage, soil retention, and habitat quality), and employing redundancy analysis to explore the influencing factors. Ecological source areas were identified, and the Sustainable Development Goals (SDGs) score was calculated to systematically evaluate the contribution of nature reserves. The results indicate that from 1990 to 2010, the built-up area of Panjin increased by approximately 159%, leading to a reduction in carbon storage, soil retention, and habitat quality by 20%, 4%, and 14%, respectively. From 2010 to 2020, ecological restoration policies resulted in a 63% increase in ES compared to 2010. Nature reserves played a crucial role in maintaining ecological stability, providing over 40% of the ecological source areas while occupying only 24% of the city’s area and contributing more than 30% to the overall urban ecological sustainability. This study is the first to systematically assess the multiple contributions of nature reserves to urban ecological sustainability, providing ecological management recommendations for policymakers based on innovative environmental indicators and methods to support sustainable urban development.